Scary tales for all ages : restoring fairy tale horror through illustration : an exegesis presented in partial fulfillment of the requirements for the degree of Master of Design, College of Creative Arts, Massey University, Wellington, New Zealand - Monro, Bridget (Massey University, 2015)
Fear is a primal emotion, there are no age limits to experiencing it and yet horror, which has its roots in mythology, folklore and fairy tales, is generally restricted to adults. There is evidence to suggest, however, that the horror genre has psychological benefits for its audience as it allows them to confront their fears in a safe and fictional setting and that contrary to popular belief these benefits are not restricted to adults. Child psychologist Bruno Bettelheim believed that instead of sanitising fairy tales considered too dark for children, we should allow them to read the original darker folk versions. He argued that children were able to grapple with themes of loss, abandonment, injury and death and in so doing be better equipped to deal with challenges in real life. I aim to widen the age range typically associated with horror by creating an illustrative narrative that approaches the genre with both adults and children in mind. To do this I am retracing the roots of horror in fairy tale texts that resonate with all ages and which deal with universal themes and fears. In particular, my project investigates how illustration can be applied to the fairy tale The Pied Piper of Hamelin to reprise the darkness of the early Brothers Grimm narratives.
Keywords: Monro, Bridget; Criticism and interpretation; Children's literature; Illustrations; Horror in art